Differences in care between younger and older patients in the 2019 English national memory service audit. (December 2022) - Cook, Laura D.; Souris, Helen; Isaacs, Jeremy D.
Abstract : Aims and method: This paper analyses how practice varied between patients aged <65 and ≥65 years in the 2019 UK national memory service audit. Results: Data on 3959 patients were analysed. Those aged <65 (7% of the sample) were less likely than those aged ≥65 to be diagnosed with dementia (23 v. 67%) and more likely to receive a functional, psychiatric or no diagnosis. Younger patients were more likely to have magnetic resonance imaging; use of dementia biomarkers was low in both groups. Frontotemporal dementia and functional cognitive disorder were diagnosed infrequently. Use of dementia navigators/advisors and carer psychoeducation was similar between groups; younger patients were less likely to be offered but more likely to accept cognitive stimulation therapy. Clinical implications: Memory services seeing younger people need expertise in functional cognitive disorder, alongside clinical skills and technologies to diagnose rarer forms of dementia. Further work is needed to understand why cognitive stimulation therapy is less frequently offered to younger people.